Biocompatible lithium zinc borate glasses activated with Sm3+/Eu3+ for glass greenhouse. Issue 12 (15th June 2022) - Vijayalakshmi, L.; Kumar, K. Naveen; Rao, K. Madhusudana; Baek, Jong Dae; Hwang, Pyung
Abstract: A series of (Sm 3+ /Eu 3+ ) co-activated lithium zinc borate glasses were procured by a fast and simple melt quenching technique to obtain remarkable red luminescent materials for glass greenhouses. The synthesized glasses are transparent under daylight and can radiate a strong reddish-orange emission under ultraviolet excitation. By exciting with 403 nm, the (Sm 3+ /Eu 3+ ) co-activated glasses exhibit enhanced ravishing reddish orange emission at 612 nm as correlated with individually (Eu 3+ ) doped glass. The reddish-orange emission pertaining to Eu 3+ ions has been remarkably enhanced by codoping with Sm 3+ ions through an energy transmission from Sm 3+ to Eu 3+ . The enhanced luminescence bands of the co-activated glasses from 580 to 700 nm were well matched with the chlorophyll absorption spectral domain. In vitro Prestoblue assay results confirm the non-cytotoxicity with appreciable biocompatibility. From the results, the procured non-cytotoxic (0.75Sm 3+ -1.0Eu 3+ ) co-activated glass has been found to be a biocompatible greenhouse glass for plant cultivation.